Investigating the Relationships between Motivation, Self-Regulation, the Learning Environment, and Cooperative Learning in Middle School Classrooms in Abu Dhabi - Rowntree, Emma Katherine (Curtin University, 2018)
My study examined 1) relationships between motivation, self-regulation, and learning environment and 2) differences in motivation, self-regulation, and learning environment perceptions for students taught by teachers effectively implementing cooperative learning and those who were not. Analysis of data from 338 middle school students in Abu Dhabi indicated: statistically significant relationships between learning environment perceptions and motivation; and more positive learning environments, motivation and self-regulation for students in cooperative learning classes when compared to their counterparts.